ANALYSIS OF DEVELOPMENT INEQUALITY AND POTENTIAL SECTORS IN THE SUBOSUKAWONOSRATEN STRATEGIC AREA DURING THE 2019-2023 PERIOD - Jiddan Nawfal Hidayat; Nenik Woyanti (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2026)
Subosukawonosraten is a strategic area in Central Java Province designed to encourage economic growth and equitable development among its regencies/cities. However, inequality remains a significant issue, particularly the disparity in income and growth rates between the core city and its surrounding areas. This study aims to examine the phenomenon of uneven development influenced by the availability of economic resources between regions, and to classify the leading economic sectors in each regency/city.This study uses secondary data from regencies/cities in the Subosukawonosraten area for the 2019-2023 period, taken from the Central Java Provincial Statistics Agency (BPS). The analysis methods used include the Williamson Index and the Theil Index to measure inequality based on GRDP and population, while the Location Quotient (LQ) and Shift-Share were used to analyze and categorize potential sectors in each region.The results indicate that the level of disparity in Subosukawonosraten regencies/cities during 2019-2023 tended to be moderate to high, and continued to rise steadily until the end of the period. The economic sectors that contribute most to the regional GRDP include agriculture in Wonogiri and Sragen Regencies; manufacturing in Sukoharjo, Sragen, and Klaten Regencies; and wholesale and retail trade in Surakarta City and Sukoharjo Regency.